Submicrometer‐Channel Organic Transistors with MHz Operation Range on Flexible Substrates by a Low‐Resolution Fabrication Technique. Issue 1 (3rd October 2022) - Spanu, Andrea; Losi, Tommaso; Mascia, Antonello; Bonfiglio, Annalisa; Caironi, Mario; Cosseddu, Piero
Abstract: In this paper, the development of a simple and reproducible approach for the fabrication of n‐type organic field‐effect transistors with a 350 nm‐long channel on flexible substrates is reported. The critical feature of the device, the channel length, is obtained using a self‐alignment process that exploits the vertical step of a plasma‐etched thin Parylene C layer, according to the so‐called step‐edge architecture. The fabricated devices can operate in continuous mode and show an average and maximum transition frequency of 2.5 MHz and 5.5 MHz, respectively. The possibility of easily obtaining high‐performing, short channel organic transistors on flexible substrates, without the use of expensive and high‐resolution techniques, represents an interesting step toward the miniaturization of flexible circuits in the field of large‐area organic electronics. Abstract : This paper, reports on the development of a low‐resolution approach for the fabrication of flexible vertical organic field‐effect transistors with submicrometer‐channel. The devices can operate in continuous mode with a maximum transition frequency of 5.5 MHz and have potential applications in the development of high‐speed flexible organic circuits, and high‐density sensor arrays for robotic skin.